3D seismic interpretation and prospect identification of the dembe field offshore, Niger delta, Nigeria - C. C, Nnaemeka; E. K, Anakwuba; F. C, Onwuagba; V. O, Nechi; C. N, Igwebudu; E. E, Ezenwa; V. C, Orabueze; F. O., Nebechukwu; A. C, Okafor (International Journal of Advanced Geosciences, 2022)
3D seismic interpretation and prospect evaluation has been carried out in a hydrocarbon bearing field, standard method of seismic interpretation which includes fault interpretation, well-seismic tie, and horizon mapping were carried out with the aid of seismic attributes such as variance edge and root mean square attributes. Well-seismic-tie established a reasonable tie and indicated that the identified reservoirs were of low impedance as the top of this reservoirs coincided with the troughs. TWT vs Depth plot showed a linear trend which aided in creating a velocity model for the time-depth conversion. Fault mapping revealed that the area was divided into 8 blocks by regionally extensive faults associated with several minor faults which are normal and listric in geometry. Petrophysical analysis showed that the reservoirs has an average porosity of 0.24, water saturation of 0.35, and net-to-gross of 0.78 which are favourable reservoir conditions. A lead Dembe-3, and 2 prospects Dembe-1 and Dembe-2 were identified. Volumetric estimation shows that the prospects boasts of a combined petroleum reserve of about 134 MMSTB of recoverable oil and about 167 BCF of recoverable gas. The results from this study show that, away from currently producing zones of the Dembe field, additional lead and prospects exist which could be further explored to optimize hydrocarbon production in the field.Â Â